Acute effects of chemoradiation on cardiac function in oesophageal cancer: a MUGA scan and echo-based study. Issue 2 (5th October 2015) - Miriyala, Raviteja; Kapoor, Rakesh; Bahl, Amit; Bhattacharya, Anish; Bahl, Ajay; Tomar, Parsee
Abstract : Objective: To study the acute effects of concurrent chemoradiation on global and regional cardiac contractility and correlate with radiation dose. Methods: 16 patients of locally advanced oesophageal squamous cell carcinoma were serially followed up with multiple-gated acquisition (MUGA) scans and echocardiograms during the course of concurrent chemoradiation to evaluate the ejection fractions (EFs) and pericardial status, respectively. Changes in cardiac contractility were correlated with the doses received by the heart. Results: Concurrent chemoradiation resulted in a significant reduction in the contractility of both left ventricle (LV) and right ventricle (RV), with a mean reduction of LVEF by 5.6% and RVEF by 6.5% over the course of treatment, which had a significant correlation with the radiation doses received by the ventricles (p=0.001). On further analysis, correlation between radiation dose and decrease in contractility was more significant in the boost phase (16 Gy in 8 fractions over one and a half weeks; p=0.001 for LV and p=0.008 for RV) compared with the initial phase (40 Gy in 20 fractions over 4 weeks; p=0.184 for LV and p=0.269 for RV). One out of 16 patients developed mild acute pericarditis. Conclusions: Concurrent chemoradiation resulted in acute decrease in EF of both ventricles in a dose-dependent manner. Correlation between cardiac doses and decrease in EF was more marked in the boost phase, suggesting a possible threshold of 40 Gy for this impairment. Nevertheless, conclusions regarding this possible threshold need to be interpreted with caution given the small sample size.